(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
أظهرت الدراسة شكلاً ناقوسياً لمسار التبخر نتح السنوي في حماه والحسكة وادلب مع وجود قمة أعظمية في تموز ونهاية أصغرية في كانون الأول أو كانون الثاني ، كما أعطت العلاقات الست المستخدمة في حساب التبخر- نتح الأساسي ثلاث مستويات من القيم أكبرها في علاقتي إيفانوف وبنمان مونتيه (الفاو) وأقلها قيم تورنوايت وحوض التبخر (نموذج A) وفيما بينهما قيم علاقتي هارغريفس ساماني وبلاني – كرايدل المعدلة. لقد كانت قيم التبخر نتح الكامن في الربيع أكبر من قيمه في الخريف في علاقات هارغريفس ساماني وبنمان مونتيه (الفاو) وكذلك حوض التبخر ( نموذج A)، أما في باقي العلاقات فكانت قيمه في الخريف هي الأكبر . مكنت الدراسة أيضاً من استخراج علاقات تراجع خطية متعددة العوامل لتقدير التبخر- نتح الأساسي الشهريّ في كلّ من حماه والحسكة وادلب اعتباراً من درجة الحرارة والرطوبة النسبية وسرعة الرياح ومدة سطوع الشمس. Annual evapotranspiration has a gaussian distribution curve notching its maximum value in July and its minimum value in December and January. As this study has shown, the six equations used to estimate potential evapotranspiration has given three levels of values, the biggest of which is demonstrated by Ivannov and FAO Penman-Monteith equations, and the smallest of which is shown by Thornthwaite and Pan Evaporation, and both of which are mediated by the values of Hargreaves and Samani, modified Blaney-Criddle equations. According to Hargreaves and Samani values, FAO Penman-Monteith and Pan Evaporation equation values, potential evapotranspiration values were bigger in spring than in autumn. But in other equations, its values in autumn were bigger. Depending on temperature, relative humidity, wind velocity, and sunshine, this study also enabled us to derive multifunctional linear regressive equations to estimate monthly potential evapotranspiration in Hamah, AL -Hasakah, and Idleb.